2018
DOI: 10.3390/min8040140
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated Inorganics in Coal Fly Ash and Bottom Ash: Calcispheres, Magnesiacalcispheres, and Magnesiaspheres

Abstract: During a study aiming to recover strategic elements and minerals from coal fly ash and bottom ash (RAREASH and CHARPHITE projects funded, respectively, by the 2nd ERA-MIN and 3rd ERA-MIN Programs of the European Union Commission), it was found that in coal fly ash and bottom ash from Romania and Poland, several morphotypes did not fit into the general fly ash classifications, unless grouped together as "undifferentiated inorganics". However, the combination of reflected light optical microscopy under oil immer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The CaO generally reacts with SO x in the boiler atmosphere, resulting in the formation of sulfate minerals in the FA and BA (Huffman et al, 1990;Moreno et al, 2005;Kostova et al, 2016). This reaction could explain the abundance of Ca-sulfate minerals (anhydrite and ettringite) in the studied FA and BA samples; however, slightly high Ca concentrations of FC samples could allow the reaction between CaO and aluminosilicate glass and Fe-oxides during combustion (Sokol et al, 2002;Vassilev et al, 2005b;Dai et al, 2014;Valentim et al, 2018). Thus, FeCa-rich glass and Ca-silicate minerals (e.g., gehlenite) in the crystalline phases were identified in the studied combustion residues (Figures 5a, 5b, 6a, 6b).…”
Section: Mineralogical Compositionmentioning
confidence: 97%
“…The CaO generally reacts with SO x in the boiler atmosphere, resulting in the formation of sulfate minerals in the FA and BA (Huffman et al, 1990;Moreno et al, 2005;Kostova et al, 2016). This reaction could explain the abundance of Ca-sulfate minerals (anhydrite and ettringite) in the studied FA and BA samples; however, slightly high Ca concentrations of FC samples could allow the reaction between CaO and aluminosilicate glass and Fe-oxides during combustion (Sokol et al, 2002;Vassilev et al, 2005b;Dai et al, 2014;Valentim et al, 2018). Thus, FeCa-rich glass and Ca-silicate minerals (e.g., gehlenite) in the crystalline phases were identified in the studied combustion residues (Figures 5a, 5b, 6a, 6b).…”
Section: Mineralogical Compositionmentioning
confidence: 97%
“…The most common method widely used to assess the diffusion coefficient of chloride in cement-based materials is the measuring of the chloride profile after a time and fitting it in Fick’s second law of diffusion [14,28]. Such a coefficient could either overestimate or underestimate the time to initiation of corrosion due to the great influence of the surface chloride concentration on the result, which changes with time leading to errors in the prediction of the diffusion coefficient of chloride based on Fick’s second law.…”
Section: Resultsmentioning
confidence: 99%
“…Given that, manufactured CBA sand with different sizes may be produced in a crushing plant. It is well known that size and particle size distribution will influence the material characteristics [12,13,14]. Other types of bottom ashes, from a municipal solid waste incinerator [15] or circulating fluidized bed combustion (CFBC) [16], are also reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There were three types of particles: spheres, agglomerates of irregular shape, and porous structures. In previous research, it was shown that spheres consists of alumosilicates and magnetite crystals are located on its surface [26,27]. Agglomerates of irregular shape consist only of alumosilicates.…”
Section: Dry Magnetic Separationmentioning
confidence: 98%